1001 things you wanted to know about Visual FoxPro - Akins, Marcia; Kramek, Andy (Hentzenwerke Pub., 2000)
1001 Things provides the granular "how-to" techniques of every area of traditional Visual FoxPro application development. It's the perfect intermediary between Hackers Guide and Effective Techniques. The Hacker's Guide to Visual FoxPro is the exhaustive command and function reference to the Visual FoxPro language. Effective Techniques for Application Development with Visual FoxPro shows you big picture and in-depth strategies for building apps. In between these two classics comes 1001 Things You Wanted to Know About Visual FoxPro. Contains over 500 pages of "tips, tricks and traps."